Improving Animal Welfare in Livestock Operations - International Finance Corporation (Washington, DC, 2015)
In the past decade, animal welfare has been increasingly recognized in importance in commercial livestock operations. Governments, academic institutions, and animal welfare professionals are addressing animal welfare at different points in the agricultural supply chain, while consumers are demanding higher standards for food safety and animal welfare. Meanwhile, regional and global initiatives to provide guidance on acceptable animal welfare practices have emerged. IFC is committed to working with clients to reduce losses, increase productivity, and/or access new markets through the application of sustainability principles, including animal welfare standards. This Good Practice Note (GPN), which supersedes the 2006 edition, contributes to IFC s continued commitment to supporting clients in a responsible and forward-looking approach to traditional livestock production (dairy, beef, broiler chickens, layer chickens, pigs, and ducks) and aquaculture in intensive and extensive systems to, among other things, help producers access and maintain entry to high quality and value market segments. This GPN describes a range of animal welfare good practice and complements IFC s Performance Standards on Environmental and Social Sustainability (2012), in particular animal husbandry requirements for IFC clients as reflected in Performance Standard (PS): biodiversity conservation and sustainable management of living natural resources. The note also describes IFC s approach to animal welfare, including details on IFC s approach to due diligence. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.